DEVELOPMENT OF REMOTE TERMINAL UNIT (RTU) FOR THE NEW FUNCTION OF DISTRIBUTION AUTOMATION SYSTEM (DAS) - Ab Ghani, Mohd Ruddin; Mat Hanafiah, Mohd Ariff; Wan Jusoh, Wan Nor Shela Ezwane; Auzani , Jidin; Raman, Siti Hajar (2012)
In this modern world, demand for electricity is in need continuously. Such this requirement is to be fulfilled every time. Electrical distribution system is where the electricity supply is received every time. This proposed intelligent system is based on a novel modeling and algorithm and the software support system. If any electrical zone is in faulty, all operational tasks will be handled by a non-expensive distribution automation system through it intelligent RTU by providing the best solutions without human intervention. Only Intelligent RTU together with the SCADA is capable to perform intelligent decisions on the distribution automation tasks. An intelligent Microcontroller based RTU for distribution automation system is proposed to innovate and renovate the downstream part of the power distribution system including the most advance communication networking system. This method utilized automation concept of creating an intelligent RTU through modification and innovations.